Exploring Wildfire Occurrence: Local Farmers' Perceptions and Adaptation Strategies in Central Côte d'Ivoire, West Africa. (7th February 2022) - Kouassi, Jean-Luc; Wandan, Narcisse; Mbow, Cheikh
ABSTRACT: Wildfires are an important ecological threat in Côte d'Ivoire with the northern half the most affected zone. This study assessed farmers' perception of wildfire occurrence in the N'Zi River Watershed and compared this perception to remotely sensed fire data trends. To this end, 259 farmers were individually interviewed and 18 farmers were involved in three focus group discussions in three agro-ecological zones. A combination of descriptive statistics and regression analysis was used for data analysis. Results showed that 78.75% of farmers observed the upward trend in the annual wildfire activity identified by remote sensing data during 2001–2016. Most of the respondents identified hunting (65.83%), farm establishment (50%) and firebreaks establishment (46.67%) as main causes of wildfires. The perceived impacts of wildfires included immediate crop burning, crop growth delaying, mid-term post-fire crop destruction, destruction of material goods and loss of human life. Local population developed endogenous strategies to cope with this scourge. Amongst identified coping strategies, firebreaks establishment and maintenance around new clearings and farms and prohibition of fire-hunting during the dry season were highlighted. Therefore, policies and institutions that support local wildfires management initiatives must take advantage of the strong community knowledge and networks to strengthen their effectiveness and sustainability.